Gravity-Model Estimation with Time-Interval Data: Revisiting the Impact of Free Trade Agreements - Peter H. Egger; Mario Larch; Yoto V. Yotov (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We challenge the common practice of estimating gravity equations with time-interval data in order to capture dynamic-adjustment effects to trade-policy changes. Instead, we point to a series of advantages of using consecutive-year data recognizing dynamic-adjustment effects. Our analysis reveals that, relative to time-interval data, the proposed approach avoids downward-biased effect estimates due to the distribution of trade-policy events during an event window as well as due to anticipation (pre-interval) and delayed (post-interval) effects, and it improves the efficiency of effect estimates due to the use of more data.
Keywords: F10; F14; 330; structural gravity; trade policy; free trade agreements; interval data